Project success - Gaer, Susan; Lynn, Sarah; Wong, Betsy Linderman; Florez, MaryAnn Cunningham; Pomann, Howard; Pomann, June; Matsunaga, Nancy Blodgett; Macpherson, Sheena M.; Bakin, Barry; Lockwood, Robyn Brinks; Santamaria, Jenni Currie; Gwynne, S. (Steve); et al. (White Plains, NY : Pearson Education, 2014)
Project Success is a blended-learning digital and print course with a strong focus on workplace skills, career readiness, and 21st century challenges. This unique video-based series engages learners with high-interest video vignettes that represent a "day in the life" of characters in diverse workplace settings that may simulate their own. Integrated skills lessons encourage critical thinking and problem solving woven into the students' English language learning journey.
Intro / Sarah Lynn -- 1 / Betsy Wong, MaryAnn Florez -- 2 / Howard Pomann, June Pomann -- 3 / Nancy Blodgett Matsunaga, Sheena M. Macpherson -- 4 / Barry Bakin, Robyn Brinks Lockwood, Jenni Currie Santamaria -- 5 / Steve Gwynne, Ingrid Greenberg, Jennifer Bixby.
Keywords: English language -- Textbooks for foreign speakers; English language -- Spoken English; English language -- Sound recordings for foreign speakers; English language -- Study and teaching -- Foreign speakers -- Audio-visual aids; Business communication -- United States -- Vocational guidance